Manajemen Softskills: Penguatan Kompetensi Analisis Data Penelitian Berbasis SPSS bagi Mahasiswa Manajemen - Wawan Ruswandi; Angga Pramadista Sudrajat; Euis Lisnawati; Noornissa Sarah Ginanjar (Universitas Prof. Dr. Moestopo (Beragama), 2026)
The development of science and technology requires students to have the ability to process and analyze research data systematically, accurately, and using technology. However, the results of observations of students in the Management Study Program at Linggabuana University PGRI Sukabumi indicate that data analysis skills using SPSS still need improvement, especially in instrument testing, selection of analysis techniques, and interpretation of statistical output. This Community Service activity aims to improve students' competence, independence, and digital statistical literacy through SPSS-based training. The implementation method uses a participatory-educational approach through hands-on training, which includes needs observation, material preparation, direct practice training, data analysis assistance, and evaluation through pre-tests and post-tests. The activity was carried out on May 3 and 10, 2026, involving 150 students. The evaluation results showed an increase in participant competence, with an average achievement of 83.4% in the good category, especially in aspects of presentation of analysis results, validity and reliability tests, and use of SPSS. In addition, there was an increase in the ability to interpret output and independence in research data analysis. This activity has proven effective in enhancing data analysis skills and supporting the improvement of students' research proposals and theses in a more systematic and data-driven manner.